Lazarino de Manosco : une écriture féminine multiforme à la fin du xixe siècle - Sylvan Chabaud (Revue des Langues Romanes)
At the end of the 19th century, Lazarine Nègre, a Manosque woman living in Marseille, wrote numerous articles and poems in the langue d'oc for the newspaper La Sartan or L'Aiòli of the Félibrige and became known to Frédéric Mistral and Paul Arène, among others. A large part of his writings were collected and published by Paul Ruat in 1904. We will try to highlight the main forms of writing chosen by this woman of Provençal Letters. How is this corpus organized, which at first sight seems fragmented? We will take into account the numerous texts gathered, after her death, in a collection entitled Li Remembranço, but also the manuscripts and notably a theater play. It is by exploring three main forms that we propose this discovery of Lazarine's writing : first of all his poetic pen (poems and songs), then his pronounced taste for prose (memories and accounts of daily life) and finally his theatrical experience (through an unpublished drama : Amour de maire).